AutoEvoChem V2.0 – A Smart Molecular Simulation & Synergy AI Toolkit for Computational Chemists and Biopharma Researchers - Barack Ndenga (My University, 2025)
AutoEvoChem V2.0 is an AI-powered software combining molecular generation, pharmacological synergy prediction, 3D visualization, and intelligent simulation for drug discovery and advanced research...
AutoEvoChem V2.0 is an AI-powered software combining molecular generation, pharmacological synergy prediction, 3D visualization, and intelligent simulation for drug discovery and advanced research...